Atendimento educacional especializado: dimensão política, formação docente e concepções dos profissionais - Buiatti, Viviane Prado (2013)
Due to the intensification of public policies, especially from the 1990s on inclusive education, issues such as the participation and rights of all in regular school, its restructuring, as well as special school as the center of discussion brought the Specialized Education Services (SES) that should be performed preferably in regular schools of education. In 2008 comes the first decree which stipulate for special education and the Specialized Education Services (SES), but it was revoked in 2011 by Decree No. 7611 of November 17, 2011. This study aimed to analyze some legal documents that portray public policy of inclusive education and special education, and it was based mainly Decree No. 7611 which stipulates the SES. In addition to reflecting on the dimensions of inclusion / exclusion, the use of expressions: difference, diversity and others, and finally, the schooling of all, taking as reference the cultural-historical theory. Added to these analyzes, interviews were conducted with professionals from two different public schools, that includes SES teachers, regular teachers and SES supervisors. Documentary analysis showed that the education system inclusive without discrimination and guided by equal opportunities is a duty of the state. The records also set the definition of the target audience of the SES as people with disabilities, pervasive developmental disorders and high ability or giftedness. The SES is offered in opposite time of regular classes, so the students attend regular classroom, and they can regularly attend this school, and have access to all the classes. The SES activities are a complement and / or supplement to schooling. Accessibility is central expression in the texts discussed and it involves aspects such as architectural structure, communicative, methodological, conceptual and attitudinal. The Ministry of Education has several actions for the enforcement of accessibility in the process of inclusion and education of all people in the education system, promoting programs for accessibility and training of teachers. The legal documents highlight the roles of professionals in the SES and ensure the continuing education of teachers as a right and duty of them. The field research observed how the SES is set in schools, and there is a consensus that the program contributes to the education of students. However, the participants emphasized some limitations and problems working with SES. Featuring: 1) the difficulty of dialogue between the modalities of education (regular teaching and teaching in SES classrooms), 2) lack of material to work with demand, 3) inadequate physical space, 4) the absence of continuing education, mainly for regular teachers, 5) difficulties related to educational assessment of students and the organization of the intervention plan. Considering these aspects, the writings differ from the reality of everyday life schools, so that educational institutions must review their ideas and actions to promote access, learning, equal conditions, restructuring and reorganizing educational structures in order to carry out the education of all students and do actions to prevent segregation and discrimination. All reflections on these issues need to be guidelines relentless in continuing education of teachers.